Novel antimicrobial coating for hernia meshes - Klaus Dieter Kühn; Débora C. Coraça-Huber; Michael Erdtmann; Gerwin A. Bernhardt; Christian Fölsch (Frontiers in Cellular and Infection Microbiology)
PurposeAntibiotic coating for several medical devices has been carried out; however, there are only few studies about coating hernia meshes with antimicrobial substances. In this study we checked the capacity of different commercially available hernia meshes to act as drug carrier.MethodsThe meshes were coated with gentamicin palmitate, chlorhexidine palmitic acid and chlorhexidine palmitate. The coating mass and subsequent in vitro delivery rate were evaluated for gentamicin palmitate by fluorescence polarization. For Chlorhexidine coated devices the coating mass was determined by weighing. The in vitro delivery rate was determined by UV absorption (255 nm). The interaction of each mesh to the different coating substances was observed by scanning electron microscopy.Results1. Certain uniformity was observed on the quantity of chlorhexidine coating the surface of each mesh used when compared with gentamicin palmitate coating. 2.We did not detect significant difference between the amounts of gentamicin palmitate released from each mesh. 3. The release of chlorhexidine palmitate and chlorhexidine palmitic acid from UltraPro™ and Mersilene™ were significantly higher (p<0.05) in comparison with the other two meshes. 4. The coating substances covered the surface of the fibers without damaging its structure. 5. The coating substances were distributed all along the fibers in all samples.ConclusionsWe suggest the use of chlorhexidine palmitate and chlorhexidine palmitic acid, as well as gentamicin palmitate, for coating of hernia meshes aiming prevention of infections. Further investigation of the bactericidal effect of coated hernia meshes against biofilm form of S. aureus and other device-related infections is suggested.